2012
DOI: 10.1111/j.1525-1470.2012.01781.x
|View full text |Cite
|
Sign up to set email alerts
|

Resolution and Recurrence of Vitiligo Following Excision of Congenital Melanocytic Nevus

Abstract: Vitiligo associated with halo congenital melanocytic nevus (CMN) is rare. There are limited reports in the literature, especially with regard to CMN excision. We present the case of a 5-year-old girl who presented with vitiligo of the periorbital and axillary regions and halo formation around CMN of the buttock. The lesion was excised, and all areas of vitiligo improved, but 18 months postoperatively, a halo of depigmentation appeared around the excision scar and later in the periorbital and axillary regions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…While for long it was believed that both share a common immunological mechanism of pigment destruction, recent studies point toward their separate pathogenic mechanism. [5] The support to the hypothesis comes from an observation made by Workman et al . [5] who reported a recurrence of vitiligo lesions after their initial regression on the complete removal of nevi.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…While for long it was believed that both share a common immunological mechanism of pigment destruction, recent studies point toward their separate pathogenic mechanism. [5] The support to the hypothesis comes from an observation made by Workman et al . [5] who reported a recurrence of vitiligo lesions after their initial regression on the complete removal of nevi.…”
mentioning
confidence: 93%
“…[5] The support to the hypothesis comes from an observation made by Workman et al . [5] who reported a recurrence of vitiligo lesions after their initial regression on the complete removal of nevi. Other observations that support for different triggers for halo nevi and vitiligo are that while halo nevi always begin around a nevus, vitiligo rarely does so; a lymphocytic infiltrate is always present in halo nevus but is exceptional in lesions of vitiligo.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Microstructural transformation and cellular injury progresses into multiple whitish patches after occurrence of halo nevus. van Geel et al [4] conjectured improvement in skin lesion after early surgical excision and Workman et al [15] observed initial improvement after excision of a halo nevus arising in congenital melanocytic nevus. However, elucidation must be supported through sufficient cases and studies.…”
Section: Concurrent Vitiligo In Congenital Halo Nevusmentioning
confidence: 99%